Compatibility of Latvian non-conviction-based confiscation with Convention on Human Rights - Lemberskis, Artjoms (Riga Graduate School of Law, 2022)
Traditional “repressive” criminal law is no longer sufficient to deal with the new threats posed by the global risk and information society. New forms of combatting international organised crime, drug trafficking and other serious crimes have emerged to target the most crucial aspect of incitive of the criminals – their money. Deprivation of property illegally obtained is an essential tool for crimes and money laundering. It led to the question of whether it is by human rights to confiscate the proceeds of crime, detected merely, e.g., in the form of suspects’ unexplained wealth, under a concept of unjust enrichment and re-establishment of the situation before a crime, and to do so without a conviction and by applying a set of less strict “civil”-law evidentiary rules. The primary focus will be to study the compatibility of the Latvian non-conviction-based confiscation with the European Convention on Human Rights and European Court of the Human Rights case law. The principles of the ECtHR will be examined to find out the court’s position regarding non-conviction-based confiscations and to define the adequate procedural safeguards that should be in place to comply with the European Convention on Human Rights. The thesis topic is if the Latvian legal acts of special confiscation of property can violate Article 6 and Article 1 of Protocol 1 of the European Convention on Human Rights and what procedural safeguards should be respected and taken into consideration to comply with the European Convention on Human Rights. Additionally, this paper will examine the experience of other countries, which have long-standing practices in implementing similar mechanisms in combating money laundering and organised criminal groups.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Criminal law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Confiscation; European Convention on Human Rights; Latvia